Propagation studies in Smilax fluminensis Steud. (Smilacaceae) - Soares,Anielca Nascimento (2011)
Smilax L. species, popularly known in Brazil as salsaparrilha, have been used in folk medicine as tonic against rheumatism and as anti-syphilitic since the sixteenth century; however, until today, their roots have been explored in an extractive way. The aim of this study was to analyze the propagation of Smilax fluminensis aiming to meet the demand and to propose procedures for its sustainable management. It was analyzed the percentage of seed germination, rooting of aerial and subterranean stem cuttings and plant resprouting capacity after removal of the shoots. The monitoring lasted one year. Seeds were subjected to temperatures: 25°C, 30°C, 20-30°C and 20-35°C under a daily photoperiod of eight hours and in the absence of light. For rooting the stem cuttings, aerial and subterranean stems about 20cm long with two nodal regions were subjected to treatment with distilled water (control) and indolbutyric acid (IBA) at 100ppm. The best germination percentages obtained for S. fluminensis were 80% at 20-30°C under light and 85% at 30°C in the dark. Only subterranean stem cuttings showed significant difference concerning fresh and dry matter of roots with higher values in treatments with hormone compared to the control.